Analisis Multidimensional Scalling untuk Keberlanjutan Usahatani Bawang Merah di Kecamatan Sianjur Mulamula Kabupaten Samosir - Siregar, Aflahun Fadhly; Salsabila; Pirngadi, Rahmat Suryanto (Universitas Medan Area, 2025)
Shallots have been a prime commodity in North Sumatra. The well-known cultivation center for shallots in North Sumatra is around Lake Toba, located at an altitude of 900 to 2000 meters above sea level, specifically in Samosir Regency. Sianjur Mulamula District is one of the main shallot-producing areas in Samosir Regency. This study aims to identify the factors affecting the sustainability of shallot farming and assess the sustainability status of shallot farming in Sianjur Mulamula District, Samosir Regency. The research method employed is Multi-Dimensional Scaling (MDS), evaluated from the Ecological, Economic, Socio-Cultural, Technological, and Institutional dimensions. The analysis results show that the sustainability index of shallot farming is 49.02, indicating a less sustainable condition. Further analysis identifies several sensitive attributes influencing the sustainability of shallot farming based on different dimensions. In the ecological dimension, the sensitive attributes include land suitability, land compatibility, and land potential. In the economic dimension, price is a key factor affecting sustainability. Meanwhile, the social dimension highlights the importance of family participation in the farming process. In the technological dimension, the processing industry is a significant sensitive attribute, and in the institutional dimension, extension activities play a crucial role in supporting sustainability. These findings are expected to provide recommendations for developing more sustainable policies and practices in shallot farming.